Mobility justice in low carbon energy transitions. (August 2016) - Mullen, Caroline; Marsden, Greg
Highlights: Identifies social injustice associated with dominant, technological approaches to tackling transport pollution. Examines means of reconciling of environmental and social aspects of mobility justice. There is potential for justice in a move to mobility less reliant on powered vehicles. Mobility justice requires thinking beyond provision of access to resources. Justice requires collective decisions about which activities involving mobility are valued and accommodated. Abstract: Mobility systems raise multiple questions of justice. Work on mobility justice and policy often treats different elements of the debate separately, for example focussing on environmental justice or accessibility. This is problematic as it can privilege policy solutions without a full view of the winners and losers and the values implicit in that. Using analysis of current policy, we investigate how mobility justice can reconcile its different components, and find two major consequences. First, is doubt about the justice of the existing policy approach which tries to tackle transport pollution primarily through a shift to low emission vehicles. This approach privileges those with access to private vehicles and further privileges certain sets of activities. Second is a need to reassess which basic normative ideas should be applied in mobility justice. Work on mobility justice has tended to appeal to conceptions of justice concerned with access to resources including resources enabling mobility. These conceptions say little about how resources should be used. We show that avoiding stark inequalities means collectively thinking about how resources are used, about how we value activities involving mobility, and about what sorts of goods and services we create.